DESCRIPTIVE ANALYSIS OF THE IMPLEMENTATION OF THE HEPATITIS B EARLY DETECTION PROGRAM IN PREGNANT WOMEN IN THE HEALTH OFFICE OF NORTH SUMATRA PROVINCE USING THE CIPP MODEL IN 2023 - Ungsi Maranatha Padang; Susy Sriwahyuni; Perry Boy Chandra Siahaan; Dian Fera; Siti Maisaroh Fitri Siregar (PT. Radja Intercontinental Publishing, 2024)
The achievement of pregnant women implementing DDHB in North Sumatra province in 2023 was 37.37%, not yet reaching the target of 95% and North Sumatra is the province with the lowest achievement in Indonesia in 2020-2022. The aim of the research is to provide an overview of the implementation of the DDHB program for pregnant women using CIPP theory. The research uses qualitative methods with a descriptive approach and evaluative design. The informants consisted of a key informant, namely PJ hepatitis, 2 main informants, namely hepatitis staff and a supporting informant, namely the head of the P2PM section. PThere is an aspect of the context of not achieving the target of pregnant women implementing DDHB due to the impact of previous Covid-19, pregnant women doing many visits 1 at health facilities such as clinics which do not report to the health service, and Padang Sidempuan, West Nias and Nias Regencies do not carry out DDHB . In the input aspect, budget shortages cause limitations in carrying out interventions. In the process aspect, there was a delay in reporting by districts/cities due to the inability to use the Sihepi application so it was done manually. In the product aspect, pregnant women implementing DDHB did not reach the target, namely 37.37%, with the 2023 RENSTRA target of 95%, and districts/cities implementing DDHB did not reach the target, namely 93.93%, with the 2023 RENSTRA target of 100%, and the achievement of Hepatitis B reactive pregnant women in 2023 is 0.83, indicating a decrease from the previous year of 1.1%. ImplementationDDHB for pregnant women in North Sumatra Province has not gone well. So that it is necessary to carry out in-depth advocacy, outreach, surveys and interventions with all parties involved such as pregnant women, health workers in health facilities, and district/city health offices, and increase cross-sector collaboration.